2002
DOI: 10.1007/s00359-001-0262-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity thresholds of juvenile loggerhead sea turtles ( Caretta caretta ): an electrophysiological approach

Abstract: Visual evoked potentials measure dynamic properties of the visual system by recording transient electric responses of neural tissue identified to correspond to a specific visual stimulus, such as light or a striped grid. In this study, visual evoked potentials were used to test the visual acuity of juvenile loggerhead sea turtles (Caretta caretta) in water. Subject animals were fitted with a Plexiglas goggle filled with filtered seawater. Stimuli of black and white striped gratings were presented to the turtle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…Anatomical and electrophysiological studies have suggested that sea turtles have well-developed visual systems that provide better visual acuity in water than in air [75]. Under laboratory conditions, the underwater visual acuity of juvenile loggerhead turtles was estimated at 5.38 and 12.89 min of arc by using electrophysiological [76] and behavioural [77] approaches, respectively, suggesting that loggerhead turtles are capable of visually discerning prey underwater [76], [77]. If turtles use visual cues to detect prey, movements during mid-water foraging events should change depending on the intensity of the ambient light.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical and electrophysiological studies have suggested that sea turtles have well-developed visual systems that provide better visual acuity in water than in air [75]. Under laboratory conditions, the underwater visual acuity of juvenile loggerhead turtles was estimated at 5.38 and 12.89 min of arc by using electrophysiological [76] and behavioural [77] approaches, respectively, suggesting that loggerhead turtles are capable of visually discerning prey underwater [76], [77]. If turtles use visual cues to detect prey, movements during mid-water foraging events should change depending on the intensity of the ambient light.…”
Section: Discussionmentioning
confidence: 99%
“…Leatherback sea turtles are known to possess a visual streak along the nasotemporal retinal axis and an area temporalis of the dorsotemporal retina which corresponds to improved acuity and detection of prey of the visual field in front, ventral and lateral to the Leatherback's head and mouth 45 . Green and Loggerhead turtles also possess a visual streak, 45,46 and visual acuity thresholds measured in juvenile Loggerheads have been analogous to other benthic, shallow water species 47 …”
Section: Discussionmentioning
confidence: 99%
“…Behavioral and physiological studies have shown that visual cues are likely to play an important role during sea turtle foraging behavior (Moein- Bartol et al 2002, Constantino & Salmon 2003, Moein-Bartol & Musick 2003, Swimmer et al 2005, Southwood et al 2008. Recent laboratory experiments indicate that lightsticks used on pelagic longlines influence loggerhead sea turtle orientation and swimming behaviors .…”
Section: Introductionmentioning
confidence: 99%